Expression and activity of key lipases during the larval development of walking catfish (Clarias magur). Issue 5 (20th June 2019) - Mir, Ishfaq Nazir; Srivastava, P. P.; Bhat, Irfan Ahmad; Dar, Showkat Ahmad; Sushila, Ngairangbam; Varghese, Tincy; Muralidhar, A. P.; Jain, K. K.
Abstract: The study was conducted to investigate the expression and activity of key lipolytic enzymes during the ontogenetic development of Clarias magur . After partial characterization, the messenger RNA (mRNA) expression analysis of lipoprotein lipase (LPL), pancreatic triacylglycerol lipase (PL), and bile salt‐activated lipase (BAL) genes along with the specific lipase activity were performed in larvae from Day 1 after hatching till 34‐day posthatch (dph). Heterogeneous patterns of mRNA expression were shown by the important lipolytic enzymes and were detected before first exogenous feeding during the yolk‐sac stage. LPL started increasing from 13 dph and peaked at 16 dph followed by a declining trend till 34 dph. However, the PL observed to be peaking at 9, 22, and 30 dph. Similarly, BAL showed an increasing trend from 11 to 22 dph with a significantly high level of mRNA expression at 16 dph. Later, the specific lipase activity was evaluated which appears at Day 1 after hatching with a progressive increase from 7 to 16 dph and a further declining trend afterwards with a peak at 22 dph. The results indicated the development of exocrine pancreas at 16 dph. Furthermore, the transcript levels and the activity of lipases were regulated with the age. Hence, the present study can be helpful in devising different strategies containing optimum lipid levels at a suitable stage of development for improving the survival during larval rearing. Furthermore, the study could be a baseline for elucidating the optimized dietary lipid levels of this catfish during its larval rearing. HIGHLIGHTS: The partial cDNA encoding LPL, PL and BAL were cloned from C. magur . Although the expression and activity of respective lipases was detected before the exogenous feeding, however, the peaks were observed at 16 dph The transcript levels and the activity of lipases were regulated by age and C. magur larvae are capable of utilizing dietary lipids from 13 dph onwards Abstract : Molecular characterization and expression of lipolytic genes during the ontogenetic development of Indian walking catfish ( Clarias magur ).